SELECTION OF SOCIAL MEDIA PLATFORMS USING FUZZY PROMETHEE METHOD WITH DIFFERENT SCENARIO TYPES - MELİKE KÜBRA EKİZ BOZDEMİR; ATAKAN ALKAN (Journal of Engineering Studies and Research)
Social media are widely and mostly utilized in many areas to increase advertising, client relations, tourism, journey and many others by means of members or organizations. Social Media Platforms (SMPs) are becoming increasingly popular in the world. The selection of SMPs, which might be widely and mostly utilized by members or organizations, becomes a critical and complex problem. Moreover, some problems that need to be investigated which consist of the reason for the use of different SMPs, purpose, and frequency of use. In this study, we have investigated to explain these problems via questionnaire which evaluates by undergraduate pupils (N = 173). Therefore, we have created twelve different scenarios that are different weights and thresholds and handled the selection and ranking of SMPs by fuzzy Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) I and II. Consequently, we able to conclude that "Which SMPs were more preferred?", "What are the reasons for selection of SMPs? and "Which criteria are more important for this selection?". In addition, this study can be guiding an infrastructure for the content of new SPMs in the future.